KARAKTERISTIK BLOK PLASTIK BAHAN PASANGAN DINDING (BPBPD) MENGGUNAKAN MINYAK JELANTAH DAN PLASTIK TIPIS BEKAS KEMASAN DENGAN MATERIAL PENGISI AGREGAT ALAM - Mataram, I Nyoman Karnata; Thanaya, I Nyoman Arya; Manurung, Edwin Christiansen (Jurnal Ilmiah Teknik Sipil; Vol 27 No 2 (2023): Jurnal Ilmiah Teknik Sipil, Vol. 27 No. 2, September 2023, 2023)
The production of waste continues to increase along with population growth. Waste plastic wrap and waste cooking oil are some of them. These materials can be used as Plastic Wall Block (PWB). The objective of this experiment was to analyze the properties of PWB that utilize waste cooking oil, waste plastic wrap and natural aggregates. This study used 3 types of mixtures namely type A mixture (Waste Cooking Oil + Crackle Plastic), type B mixture (Waste Cooking Oil + Aluminum-Coated Plastic) and type C mixture (Waste Cooking Oil + This Plastic Apart from A and B), with addition of aggregates in each mixture. After mix proportion trials, it was obtained material proportion that give the thickest mixture that can be mixed manually, was 250gr of used plastic: 250gr waste cooking oil: 1000gr aggregates, for producing sample with size of 100x100x(80-95)mm. The sample production was started by heating the waste cooking oil at temperature of 200°C, then the shredded plastics with sizes about 0,5-20mm was gradually poured then add the aggregates and mixed it manually and evenly, then molded with with metal mold. The melted plastic was compacted using a Marshall hummer at 2 blow at ideal temperature of 125-110°C, to give light densification effect and even surface. The sample was cooled down, then taken out of the mold and tested. It was obtained that the initial rate of suction (IRS) ranged from 0,0119-0,0833 kg/m 2 .min; water absorption ranged from 1,59-3,93%; and porosity ranged from 1,041-1,819%. The average un-soaked compressive strength of mixture A, B and C was 42,49; 5,61; 5,95 kg/cm 2 consecutively, and the soaked compressive strength was 30,93; 4,25; 3,40 kg/cm 2 . In general, the compressive strength of PWB type A in the un-soaked condition meets the requirements for the minimum compressive strength of solid concrete bricks according to the Indonesian National Standar (SNI-03-0349-1989) quality IV (=25 kg/cm 2 ), comparable to the other low compressive strength wall materials.